The crowd funding services handbook : raising the money you need to finance your business, project, or invention - Rich, Jason (Hoboken, New Jersey : Wiley, 2014)
"Crowdsource funding is the new way to finance start-ups in a networked worldEntrepreneurs, small business owners, investors, artisans, or those who merely have a good idea for a business venture have a new and attainable means of securing capital to grow their dreams. Gone are the days when the only options to raise funds for a new business were venture capitalists, angel investors, or Wall Street. Web-based crowdfunding services are now plentiful and offer a variety of options for the aspiring entrepreneur. However, these services are not typically as well-understood as the more traditional means of raising capital. In The Crowdsource Funding Services Handbook, author Jason R. Rich offers a step-by-step overview of the various crowdsource funding services available on the Web, as well as the necessary documentation required to launch a successful crowdfunding campaign. Contains details on how to evaluate and select the best online platform for crowdfunding efforts Provides details on creating a business plan to the specifications require to raise capital via crowdfunding Provides an overview of the financial projections that will be required for a crowdfunding initiative Proposes a specific approach to creating a "pitch video" to succeed with a crowdsource funding campaign The Crowdsource Funding Services Handbook is a thorough, well-developed resource for those seeking to raise capital to start a business or fund the development of an innovative idea. Author and crowdfunding expert Jason R. Rich provides this definitive, hands-on guide to raising capital in the new economy"--
"Discusses the pros and cons of some of the most popular crowdsource funding services, and walks the reader through the process of using one of these services to fund their idea"--
How crowdfunding works: the basics -- What types of businesses, projects, and inventions can get funded -- Introduction to crowd funding platforms and services -- Preplanning your crowd funding campaign -- Crunching the numbers -- Targeting your backers and supporters -- Producing your promotional video -- Promoting you campaign -- Interacting with your backers using a blog -- Getting the help you need -- You've reached your funding goal: now what? -- Get started using kickstarter.com -- Interviews with crowd funding experts -- Crowd fuding experts share their secrets -- Experienced crowd fundrs share their secrets.
Includes index.
Includes bibliographical references and index at the end of each chapters.
Print version record and CIP data provided by publisher.
Keywords: Crowd funding; Venture capital; New business enterprises -- Finance; BUSINESS & ECONOMICS -- Investments & Securities; Crowd funding; New business enterprises -- Finance; Venture capital; Electronic books